Efficacy of phytoestrogens for menopausal symptoms: a meta-analysis and systematic review. (April 2015) - Chen, M-N.; Lin, C-C.; Liu, C-F.
Abstract: Objective To perform a meta-analysis examining the efficacy of phytoestrogens for the relief of menopausal symptoms. Methods Medline, Cochrane, EMBASE, and Google Scholar databases were searched until September 30, 2013 using the following key words: vasomotor symptoms, menopausal symptoms, phytoestrogens, isoflavones, coumestrol, soy, red clover. Inclusion criteria were (1) randomized controlled trial (RCT), (2) perimenopausal or postmenopausal women experiencing menopausal symptoms, (3) intervention with an oral phytoestrogen. Outcome measures included Kupperman index (KI) changes, daily hot flush frequency, and the likelihood of side-effects. Results Of 543 potentially relevant studies identified, 15 RCTs meeting the inclusion criteria were included. The mean age of the subjects ranged from 49 to 58.3 and 48 to 60.1 years, respectively, in the placebo and phytoestrogen groups. The number of participants ranged from 30 to 252, and the intervention periods ranged from 3 to 12 months. Meta-analysis of the seven studies that reported KI data indicated no significant treatment effect of phytoestrogen as compared to placebo (pooled mean difference = 6.44, p = 0.110). Meta-analysis of the ten studies that reported hot flush data indicated that phytoestrogens result in a significantly greater reduction in hot flush frequency compared to placebo (pooled mean difference = 0.89, p < 0.005). Meta-analysis of the five studies that reported side-effect data showed no significant difference between the two groups ( p = 0.175). Conclusion Phytoestrogens appear to reduce the frequency of hot flushes in menopausal women, without serious side-effects.